The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages out in the penal system, and there is controversy as to what form these should take. We should however regard social provision for the delinquent as a public responsibility, and as a social service rather than as a penal system, and this is particularly important for young people. The criminal courts are patently in need of reform and we can see some immediate steps which could be taken. We could begin with changes in the method of appointing justices; it should be compulsory for workers' organisations to be represented on the bench, and for some form of democratic control of justices to be operated. While it is not within the scope of this pamphlet to dicuss [discuss] in any detail the reform of the legal system, we consider that the principle that justice should be free to all should be adhered to in civil as well as in criminal courts. 10. Special problems of the normal person Everyone meets with emergencies of some kind which cannot be foreseen and covered by any system, and a good deal of the time of a social worker dealing with normal people is taken up with advising them in such emergencies, or telling them where the advice and help which they need may be obtained. Such institutions as the Citizens' Advice Bureaux have been set up particularly to deal with the emergencies of war, but they deal also with those which might just as easily arise in peace. 20 15X/2/464/1